Influence of lipoflavon on regeneration of traumatized sciatic nerve at different schemes of injection. - Khrapay, O. V. (Морфологія / Morphologia / Morfologìâ, 2010)
The problem of regeneration of nerve fibers attracts attention of many researchers, because the damage of peripheral nerves results in disability, particularly in young age. For this purpose, breaches of different morphological structures of peripheral nerve under complete neurotomy in experiment on rats and their pharmacological correction by lipoflavon at different schemes of injection were investigated. We used methods of light microscopy and morphometry. Lipoflavon is a medicine, which is presented by the liposomal form of quercetin. Rats were injected with lipoflavon (0,1 mg/kg, Biolek, Kharkov) during ten days. Improvement of regeneration of nerve fibers of damaged nerve was observed after 12 weeks at injection of the medicine on the early stages of recovery and at combination of early and late periods. Morphological changes, which were observed under these two schemes, did not differ substantially with each other. So we considered the expediency of lipoflavon use on the early stage of posttraumatic period.